Patient-level benefits associated with decentralization of antiretroviral therapy services to primary health facilities in Malawi and Uganda. Issue 1 (10th January 2018) - Abongomera, George; Chiwaula, Levison; Revill, Paul; Mabugu, Travor; Tumwesige, Edward; Nkhata, Misheck; Cataldo, Fabian; van Oosterhout, J; Colebunders, Robert; Chan, Adrienne K; Kityo, Cissy; Gilks, Charles; et al.
Abstract: Background: The Lablite project captured information on access to antiretroviral therapy (ART) at larger health facilities ('hubs') and lower-level health facilities ('spokes') in Phalombe district, Malawi and in Kalungu district, Uganda. Methods: We conducted a cross-sectional survey among patients who had transferred to a spoke after treatment initiation (Malawi, n=54; Uganda, n=33), patients who initiated treatment at a spoke (Malawi, n=50; Uganda, n=44) and patients receiving treatment at a hub (Malawi, n=44; Uganda, n=46). Results: In Malawi, 47% of patients mapped to the two lowest wealth quintiles (Q1–Q2); patients at spokes were poorer than at a hub (57% vs 23% in Q1–Q2; p<0.001). In Uganda, 7% of patients mapped to Q1–Q2; patients at the rural spoke were poorer than at the two peri-urban facilities (15% vs 4% in Q1–Q2; p<0.001). The median travel time one way to a current ART facility was 60 min (IQR 30–120) in Malawi and 30 min (IQR 20–60) in Uganda. Patients who had transferred to the spokes reported a median reduction in travel time of 90 min in Malawi and 30 min in Uganda, with reductions in distance and food costs. Conclusions: Decentralizing ART improves access to treatment. Community-level access to treatment should be considered to further minimize costs and time.